EFFECT OF LEAD - CONTAMINATED SOIL ON THE YIELD AND LYCOPENE CONTENT IN TOMATO GENOTYPES, LYCOPERSICON ESCULENTUM (MILL.) - Adewusi, O F (Research Journal of Agriculture (RJA), 2025)
This study was conducted on the "Effect of lead - contaminated soil on lycopene content and yield of tomato, Lycopersicon esculentum (Mill) genotypes". This study aimed to determine the effect of lead - contaminated soil on the lycopene content and yield of tomato genotypes. Twelve tomato genotypes utilized for this study were obtained from the tomato germplasm collection of the National Center for Genetic Resources and Biotechnology (NACGRAB), Department of Plant Genetic Resources Ibadan, Oyo-State, Nigeria. The experiment was carried out at the Teaching and Research Farm, Obakekere, Federal University of Technology, Akure, Ondo-State. The lead - contaminated soil samples were obtained from the piggery unit at the Teaching and Research Farm of the Federal University of Technology, Akure, Ondo-State. The experiment was a potted experiment with each pot filled with 5kg of lead - contaminated soil, while the control pots were filled with 5kg of normal topsoil. NGB00708, NGB00713, NGB00724, NGB00735, and NGB00737 recorded the shortest number of days to flowering (32.20 days and 32.40 days) on lead - contaminated soil and (29.20 days and 29.40 days) on uncontaminated soil, respectively. This implies that these varieties can be improved upon in future tomato breeding programs and released as early maturing varieties. NGB00752, NGB00737, and NGB00724 were found outstanding in terms of the number of fruits, individual fruit weight, and total yield per plant both on lead - contaminated and uncontaminated soil. These varieties can be improved upon and regenerated through hybridization for the production of tomato hybrids. NGB00713, NGB00725, and NGB00729 recorded high lycopene contents in lead - contaminated soil. It can be concluded from this study that lead contaminated soil retarded the growth and reduced the yield and lycopene content of tomato varieties.